2006
DOI: 10.1007/s10517-006-0383-x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and neuroprotective properties of N-docosahexaenoyl dopamine

Abstract: N-Docosahexaenoyl dopamine exhibited antioxidant activity in the test with a stable oxygen radical galvinoxyl. This compound produced a dose-dependent protective effect on cultured granular cells from rat cerebellum under conditions of oxidative stress. N-Docosahexaenoyl dopamine decelerated the development of symptoms of Parkinson's disease in mice receiving neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…One explanation for this asymmetry involves the greater availability dopamine, a neurotransmitter shown to have neuroprotective effects, in the right than in the left caudate (Bobrov et al, 2006; Shih et al, 2007; Vernaleken et al, 2007). It is possible that the increased dopamine in the right caudate reduces the vulnerability of this structure to the stress-induced neurotoxic damage associated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this asymmetry involves the greater availability dopamine, a neurotransmitter shown to have neuroprotective effects, in the right than in the left caudate (Bobrov et al, 2006; Shih et al, 2007; Vernaleken et al, 2007). It is possible that the increased dopamine in the right caudate reduces the vulnerability of this structure to the stress-induced neurotoxic damage associated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…A similar concept was described by Yehuda (2002) who suggested that N-(a-linolenoyl) tyrosine could potentially be used as an anti-Parkinson agent. Finally, Bobrov et al (2006) showed that DHA-dopamine exhibited antioxidant activity and produced a dose-dependent protective effect on cultured granular cells from rat cerebellum under conditions of oxidative stress. It also decelerated the development of Parkinson's disease-like symptoms in a MPTP (1-methyl-4-phenyl-1,2,3,6tetrahydropyridine) mouse model.…”
Section: Dopamine-and Other N-acyl-conjugates Of Dhamentioning
confidence: 98%
“…Dopamine (Shashoua and Hesse, 1996;Bisogno et al, 2000;Bezuglov et al, 2001;Bobrov et al, 2006;Ostroumova et al, 2010;Dang et al, 2011;Sakharova et al, 2012) P: rodent brain Fresh water hydra; see further text B: Hydra tissue development, mouse embryo development; uptake in mouse brain; antipyretic, analgesic, cataleptic in rats; FAAH inhibition; AEA uptake; inhibition of NO and cytokines; antioxidant and neuroprotective in rats, anti-Parkinson (see also text)…”
Section: Presence Shown In Species (P) Receptor Affinity Studies (R) mentioning
confidence: 99%
“…Bobrov et al showed that DHA-dopamine exhibited antioxidant activity and produced a dose-dependent protective effect on cultured granular cells from rat cerebellum under conditions of oxidative stress. It also decelerated the development of Parkinson's disease-like symptoms in a MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) mouse model [37].…”
Section: Cytoprotective Propertiesmentioning
confidence: 99%